Governance, corruption, and trade in the Asia Pacific region - Abe, Kazutomo, 1955- 1955- (Policy research working paper, 2008)
"This paper examines the impact of reducing corruption and improving transparency to lower trade costs in the Asia Pacific Economic Cooperation region. The authors find, based on a computable general equilibrium model, significant potential trade and welfare gains for Asia Pacific Economic Cooperation members, with increased transparency and lower levels of corruption. Results suggest that trade in the region would increase by 11 percent and global welfare would expand by